2005
DOI: 10.1021/jp0403745
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of the Interactions between Chemical Partners (Metal, Ligands, Counterions, and Support) Involved in the Design of Al2O3-Supported Nickel Catalysts from Diamine−Ni(II) Chelates

Abstract: 1.5 Ni wt %/Al2O3 catalysts have been prepared by incipient wetness impregnation using [Ni(diamine)x(H2O)(6-2x)]Y2 precursors (diamine = 1,2-ethanediamine (en) and trans-1,2-cyclohexanediamine (tc); x = 0, 1, and 2; Y = NO3- and Cl-), to avoid the formation, during calcination, of difficult-to-reduce nickel aluminate. N2 was chosen for thermal treatment to help reveal and take advantage of the reactions occurring between Ni2+, ligands, counterions, and support. In the case of [Ni(en)2(H2O)2]Y2 salts used as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 56 publications
2
60
0
4
Order By: Relevance
“…675 K) reduction of NiO to Ni 0 , as noted elsewhere. [6,42] The TPR behavior of alumina-supported nickel has been well studied [43][44][45][46][47][48] and the effect of sample pretreatment, use of different alumina substrates, and variations in Ni loading and Ni precursor have been considered. Medina et al [44] found that NiO/g-Al 2 O 3 required a higher reduction temperature compared with bulk NiO and NiO/aAl 2 O 3 , which implied a stronger interaction between NiO and g-Al 2 O 3 .…”
Section: Catalyst Activationmentioning
confidence: 99%
“…675 K) reduction of NiO to Ni 0 , as noted elsewhere. [6,42] The TPR behavior of alumina-supported nickel has been well studied [43][44][45][46][47][48] and the effect of sample pretreatment, use of different alumina substrates, and variations in Ni loading and Ni precursor have been considered. Medina et al [44] found that NiO/g-Al 2 O 3 required a higher reduction temperature compared with bulk NiO and NiO/aAl 2 O 3 , which implied a stronger interaction between NiO and g-Al 2 O 3 .…”
Section: Catalyst Activationmentioning
confidence: 99%
“…The dried impregnate is heat treated in air, called calcination, to convert the precursor into the desired metal oxide, optionally followed by a high temperature reduction treatment to obtain the metal in question. State-of-the-art studies at low Ni loadings and strong precursor-support interactions have revealed much insight into the interplay between metal, ligands, counterions and supports, and their impact on the activity, selectivity and stability of the final catalyst [13,16,17,19]. Moreover, these studies have yielded fundamental insight into the importance of liquid-solid interactions between precursor solution and support on the formation of poorly reducible mixed Ni phases like aluminates or phyllosilicates.…”
Section: Introductionmentioning
confidence: 99%
“…19,21,24 In particular, the effect of en on Ni catalysts have been studied in detail by Che et al using support powders. 18,19,[25][26][27][28] However, very few studies have been done on the effect of chelating ligands in the preparation of catalyst bodies. 15c,29 In this paper, the influence of the number of en ligands on the macrodistribution and molecular speciation of Ni 2+ in γ-Al 2 O 3 catalyst bodies during impregnation and drying has been investigated.…”
Section: Introductionmentioning
confidence: 99%